Formulation and Standardization of Face Wash Using Watermelon Rind Extract (Citrullus lanatus) - Dika Putra Wijaya; Khofifatul Rahmawati; Achmad Yusuf Bachtiar; Alverdha Elvarheta Rasseta Ridhwan; Ayu Alfianita Rahmah; Titik Taufikurohmah; Danar Danar (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The purpose of this study was to determine the utilization of watermelon rind waste as an active ingredient in the manufacture of liquid soap preparations and to obtain the best formulation of watermelon rind extract liquid soap that is physically stable. Watermelon rind waste contains many nutritious substances, such as antioxidants, that are beneficial for skin health but have not been widely utilized. This study utilizes citrulline compounds in watermelon rind, which act as antioxidants and potential vasodilators, to be used as active ingredients in the manufacture of bath soap preparations with the aim of removing dirt and stimulating blood circulation. Research method includes the preparation of thick watermelon rind extract, the preparation of salt solution, and the preparation of liquid soap preparation formulas with varying concentrations of watermelon rind extract. Evaluation includes an organoleptic test, pH, viscosity, foam height, foam stability, homogeneity, and spreadability to obtain a liquid soap formula with stable physical properties. Result showed that watermelon rind extract has the potential to be an active ingredient in liquid soap preparations in order to utilize waste and provide benefits for skin health.